Involvement of mitochondria in apoptosis of cancer cells induced by photodynamic therapy Envolvimento da mitocôndria em apoptose de células cancerígenas induzida por terapia fotodinâmica - Joselito Nardy Ribeiro; André Romero da Silva; Renato Atilio Jorge (Sociedade Brasileira de Patologia Clínica, 2004)
Photodynamic therapy (PDT), a promising cancer treatment that employs a combination of a photosensitizing chemical, oxygen, and visible light, induces apoptosis in tumor cells. However, the precise mechanism of PDT-induced apoptosis is not well characterized. Many of the photosensitizers currently in clinical or pre-clinical studies of PDT are localized in or have a major influence on mitochondria. The treatment with PDT causes mitochondrial damage and induces apoptosis through the release of cytochrome c (cyt c), apoptosis-inducing factor (AIF), Smac/DIABLO and certain procaspases. Proapoptotic and antiapoptotic members of BcL-2 family regulate the release of these proteins from mitochondria. The purpose of this mini-review is to present some recent publications that focus on the involvement of the mitochondria in apoptosis of cancer cells induced by PDT. A terapia fotodinâmica (TFD) é um promissor tratamento clínico que emprega a combinação de luz visível, oxigênio e uma substância fotossensibilizadora para tratar doenças de caráter oncológico. Esse tipo de tratamento induz a morte celular programada (apoptose) em tecido tumoral. No entanto, o mecanismo de indução de apoptose por TFD não está bem caracterizado. Muitos fotossensibilizadores possuem como alvo principal a mitocôndria. O tratamento com TFD causa danos nessa organela e induz a apoptose através da liberação de citocromo c, fator de indução de apoptose, Smac/DIABLO e certas pró-caspases. A liberação dessas proteínas, a partir da mitocôndria, é regulada por uma família de proteínas pró e antiapoptóticas, conhecida como família BCL-2. A proposta dessa minirrevisão é apresentar algumas publicações recentes que focalizam o envolvimento da mitocôndria em apoptose de células cancerígenas induzida por TFD.